Kesalahan Siswa SMP pada Soal HOTS Relasi dan Fungsi Berdasarkan Teori Kastolan Ditinjau dari Gender - Muhammad Ferdian Syah; Ulfa Masamah; Sulistya Umie Ruhmana Sari (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2026)
The low level of higher-order thinking skills in junior high school students indicates a fundamental problem that often triggers errors in solving mathematics problems. This study aims to analyze and describe junior high school students' errors in HOTS relation and function problems based on Kastolan's theory from a gender perspective. This study uses a descriptive qualitative approach involving two subjects, namely one male and one female student of grade VIII of UPT SMP Negeri 30 Gresik, selected through purposive sampling technique. Data collection through HOTS essay tests and interviews to explore students' thinking processes. Using technical triangulation data validity. The data analysis process is carried out by means of data reduction, data presentation, and drawing conclusions. The results of the study show that male students make conceptual, procedural, and technical errors, while female students do not show conceptual errors but still make procedural and technical errors. This difference indicates variations in problem-solving strategies based on gender, where male students are more impulsive and less verification, while female students are more careful but less confident. These findings emphasize the need to strengthen conceptual understanding, systematic solution steps, and accuracy to improve students' HOTS abilities.